2017
DOI: 10.1371/journal.ppat.1006225
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput genetic screen identifies previously uncharacterized Borrelia burgdorferi genes important for resistance against reactive oxygen and nitrogen species

Abstract: Borrelia burgdorferi, the causative agent of Lyme disease in humans, is exposed to reactive oxygen and nitrogen species (ROS and RNS) in both the tick vector and vertebrate reservoir hosts. B. burgdorferi contains a limited repertoire of canonical oxidative stress response genes, suggesting that novel gene functions may be important for protection of B. burgdorferi against ROS or RNS exposure. Here, we use transposon insertion sequencing (Tn-seq) to conduct an unbiased search for genes involved in resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 77 publications
0
80
0
Order By: Relevance
“…Recently, Ramsey et al used transposon insertion sequencing (Tn-seq) for a genome-wide screen and identified several factors important for resistance to NO, H 2 O 2 , and TBHP in vitro and YebC (BB0025) was identified as one of the genes that may be involved in H 2 O 2 resistance [ 78 ]. Ramsey et al also performed animal study with groups of pooled Tn mutants and found that bb0025 Tn mutant was attenuated in both mouse strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ramsey et al used transposon insertion sequencing (Tn-seq) for a genome-wide screen and identified several factors important for resistance to NO, H 2 O 2 , and TBHP in vitro and YebC (BB0025) was identified as one of the genes that may be involved in H 2 O 2 resistance [ 78 ]. Ramsey et al also performed animal study with groups of pooled Tn mutants and found that bb0025 Tn mutant was attenuated in both mouse strains.…”
Section: Discussionmentioning
confidence: 99%
“…YebC’s role in defending host ROS may also explain why the yebC mutant had a delayed infection in SCID mice observed in this study ( Table 2 ), as SCID mice have both macrophages and neutrophils that produce ROS. In addition, Ramsey et al, also showed that the gp91phox -/- mice lacking phagocyte superoxide production could not rescue the infectivity of the bb0025 Tn mutant [ 78 ]. Given that YebC controls vlsE expression discovered herein, the phenotype of the yebC Tn mutant in the gp91phox -/- mice becomes evident.…”
Section: Discussionmentioning
confidence: 99%
“…Transposon mutants were obtained from the arrayed B. burgdorferi library [54]. In order to conduct Tn-seq experiments, a single pool containing all of the Tn mutants was generated by combining sub-pools containing 70-80 individual Tn mutants each [54,96,97]. The Tn library was grown for 48 hours in the presence of kanamycin and gentamicin.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of initial studies using transposon insertion sequencing approaches focused on human pathogens, but these methods are starting to be used to examine other microbial lifestyles. Recent studies of human and animal pathogens include susceptibility and resistance of Escherichia coli to phage infection (Cowley et al, 2018), the mechanism of antibiotic binding in Staphylococcus aureus (Santiago et al, 2018), and resistance of Borrelia burgdorferi to reactive oxygen and nitrogen species (Ramsey et al, 2017). Non-pathogenic microbes are also being explored using transposon insertion sequencing methods, for example, regulation and biosynthesis of holdfast assembly has been investigated in Caulobacter crescentus (Hershey et al, 2019), circadian clock proteins have been identified in cyanobacteria (Welkie et al, 2018) and previously unknown bacterial amino acid biosynthesis genes have been identified in heterotrophic bacteria (Price et al, 2018b).…”
Section: Saturation Transposon Insertion Mutagenesis and High Throughmentioning
confidence: 99%
“…A Tn-seq study using high osmolarity, reactive oxygen species and temperature successfully identified individual E. coli genes that confer stress resistance as well as gene combinations that work synergistically to impart improved stress resistance (Lennen and Herrgard, 2014). Transposon insertion sequencing analysis of the pathogen B. burgdorferi uncovered 66 genes not previously known to be involved in resistance to reactive oxygen and nitrogen species (Ramsey et al, 2017). Conducting in vitro or in planta transposon insertion sequencing studies that incorporate rhizospheric or phyllospheric stresses could rapidly advance our understanding of the genes employed by plant growth promoting bacteria in stressful conditions.…”
Section: Future Avenues To Explore With Transposon Insertion Sequencingmentioning
confidence: 99%